(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The present article introduces the third issue of the journal entitled Gradients of liveness: socio-technical shaping of performing arts between online and offline. After situating the issue of liveness within the process of mediatization of society, and the challenges fuelled by the pandemic, we discuss the statute of the field of liveness studies. We then defend the necessity of an approach that understands liveness in terms of the “gradients” with which this phenomenon manifests itself. In the second part, the articles of the issue are presented, showing the multiple branches of the “liveness problem” through heterogeneous performative, technological and theoretical fields, thus highlighting the relevance of this theoretical tool in understanding how the sense of presence and connection is constructed in the context of mediatization.